Analysing of the Relationship between Team Cohesion and Prosocial and Antisocial Behaviors of Athletes Taking Groundwork Training in Professional Football Teams - Pepe, Osman (2021)
In this study, it was aimed to determine the relationship between team cohesion and prosocial and antisocial behaviors of football player candidates taking groundwork training in the professional football team of Kayserispor. The population of the study consisted of 172 football player candidates getting regular football training for at least 1 year in the Kayserispor football team and were in competition status, and the sample consisted of 104 volunteers. As data collection tools, “Personal Information Form”, “Youth Sport Environment Questionnaire” and “Prosocial and Antisocial Sports Participation Motives” were used. The data obtained in the study were analyzed in computer environment. Number, percentage, mean, standard deviation were used as descriptive statistical methods in the evaluation of the data. Pearson’s correlation was applied between the continuous variables of the study.Among the subtitles of youth athlete team cohesion; among the subtitles of task dimension and pro-social and anti-social behaviors, a moderate positive relationship between pro-social behavior towards teammate and a low level positive relationship between pro-social behavior against the opponent were detected. While a moderate negative relationship was detected between social behavior, there was no relationship between pro-social behavior to the opponent and anti-social behavior to the opponent, one of the subtitles of social dimension and pro-social and anti-social behavior. A low-level negative correlation was found between anti-social behavior towards teammate As a result, in Kayserispor football team, it has been observed that athletes who take groundwork training have a high level of cohesion both in terms of their duties and social aspects, they have positive attitudes and behaviors towards their teammates and the opponent both in or outside of the training or competition, regardless of the situation of the training or the competition, they think that they should stay away from humiliating and disabling attitudes and behaviors. It is thought that this is due to the strong emotional relationship among the team members and the high level of closeness to each other, and the respect they have for the opponent team players who are moving towards the same goal as themselves.